The Mediating Role of Innovation Capability on Market Orientation and Export Performance: an Implementation on SMEs in Turkey - Zehir, Cemal; Kole, Mahmut; Yildiz, Hacer (ELSEVIER SCIENCE BV, 2015)
The purpose of this study is to investigate the relationship between market orientation, innovation capability and export performance and also to figure out the mediator effect of innovation capability on the relationship between market orientation and export performance with an implementation on small and medium-sized enterprises (SMEs) in Turkey. In this context, a research model and related hypotheses have been developed. In order to test the hypotheses in the research model, a field study was carried out using the survey method with 474 owners and managers in total, from 186 number of firms operating in manufacturing sector. Data collected from 474 owners and managers have been analyzed using correlation and regression analysis with Structural Equation Model (SEM). Analysis is performed using SPSS and AMOS software packages. As a result of this study, it is founded that innovation capability has a partial mediator effect on market orientation dimensions and export performance. This empirical findings show that SMEs can be able to achieve competitive advantage through improving a market-driven innovation capability. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Innovation Capability; Market Orientation; Export Performance; SMEs; Business & Economics